Emotional Culture in in the Circular Migration of Bolivian Women in Northern Chile: Tensions, Resistance, and Intersections in Care Work (Polis (Santiago), 2021)
This article aims to analyze the emotional culture of recurrent migrant Bolivian women doing domestic and care work in Iquique. By means of a qualitative methodology that considers in-depth interviews with such migrants, the emotional records that occur in the context of care work are analyzed, identifying subjective interpretations of an emotional registrars within the framework of multiple intersecting power structures. The article gives an account of an emotional culture under the tacit conception of heteropatriarchal hierarchy, which responds to practices of social and cultural resistance in the key of a reproduction of the modern colonial gender system. These are social constructions that are deeply linked to the body logic and that in the particular case of women who carry out circular migration, the migratory status, the precariousness that this implies, as well as the subalternities inscribed in their biographies, are agenciated with dynamic and ambivalent emotional repertoires that women must perform daily in their lives and jobs.
Keywords: Emotional culture; Circular migration; migrant women; care work; intersecionality.